Exploring Lactic Acid Bacteria in Nasiriyah’s Locally Manufactured Cheese - Fatima Rashid Mohan (International Journal of Pathogens, 2024)
This investigation aimed to identify and diagnose lactic acid bacteria in locally produced cheese. Forty-eight isolates were obtained by categorizing them according to their phenotypic and microscopic features. After conducting biochemical tests, we acquired ten bacterial isolates from the Lactobacillus species. The VITEK 2 instrument was utilized to distinguish the samples to the species level with a threshold for the Lactobacillus genus. In the city of Nasiriyah, visiting the various local markets could obtain samples of locally produced cheese. The samples were placed in plastic containers, sterilized, sealed, and refrigerated. Sterile and refrigerated conditions were maintained throughout transporting samples to the laboratory.The analysis revealed that seven samples were identified as Lb. Paracasei species, with a probability range of 85 91%. Additionally, two samples could potentially be categorized as Lb. Plantarum species, with a probability of 88%. Lastly, one sample showed a likelihood exceeding 85% of being Lb. Parabuchneri. The assessment examined properties like acid production, curd firmness, and whey interactions.
Keywords: Lactic acid bacteria; Nasiriyah; VITEK 2 system. Identification; dairy product